Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/tp.0000000000000237
|View full text |Cite
|
Sign up to set email alerts
|

Serine Protease Inhibitor-6 Inhibits Granzyme B–Mediated Injury of Renal Tubular Cells and Promotes Renal Allograft Survival

Abstract: Our data show for the first time that resistance of kidney TEC to cytotoxic T-cell granzyme B-induced death in vitro and in vivo is mediated by the expression of SPI-6. We suggest that SPI-6 is an important endogenous mechanism to prevent rejection injury from perforin or granzyme B effectors and enhanced PI-9 or SPI-6 expressions by TEC may provide protection from diverse forms of inflammatory kidney injury and promote long-term allograft survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 35 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…17 Finally, the murine homolog of serine protease inhibitor-9 (serine protease inhibitor-6) was demonstrated to be renoprotective during allograft inflammation by inhibiting the activity of granzyme B. 18 Taken together, these data show excellent concordance between mRNA, protein expression, and activity data, and concordance between human and animal findings.…”
Section: Transplantation and Human -Omicsmentioning
confidence: 79%
See 1 more Smart Citation
“…17 Finally, the murine homolog of serine protease inhibitor-9 (serine protease inhibitor-6) was demonstrated to be renoprotective during allograft inflammation by inhibiting the activity of granzyme B. 18 Taken together, these data show excellent concordance between mRNA, protein expression, and activity data, and concordance between human and animal findings.…”
Section: Transplantation and Human -Omicsmentioning
confidence: 79%
“…41 Several serine proteases and their cognate inhibitors have been implicated in subclinical and clinical rejection, such as granzymes A/B and serine protease inhibitor-9. [16][17][18]43,44 More recently, it has been reported that granzyme B + regulatory B cells are increased in transplant patients, and it is suggested that these regulatory B cells may play a role in maintaining transplant tolerance and host defense. 45 SERP-1 is a serine protease inhibitor that inhibits tissuetype and urokinase-type plasminogen activators, thrombin, factor Xa, and plasmin and has been shown to inhibit early injury and chronic allograft rejection in a rat renal transplant model.…”
Section: Serine Hydrolase Enzyme Familymentioning
confidence: 99%
“…Acute kidney injury is a critical syndrome caused by ischaemic or renotoxicity insults and is characterized by acute tubular necrosis and renal dysfunction . Improving the renal tubular epithelial cell (TEC) regeneration and functional recovery has been considered as a key to attenuating the outcome of AKI . Previous studies have suggested that stem cells, such as bone marrow‐derived mesenchymal stem cells (BMSC), could be incorporated into post‐ischaemic renal tubules or enhanced tubular survival .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, activated cytotoxic T cells are known to play an important role in the inflammatory activity and destruction of allograft tissue (9). The increased presence of cytotoxic granules such as granzyme B have been associated with acute rejection (10)(11)(12). Similarly, FoxP3 + T cells [T regulatory cells (Tregs)] have been identified as potential crucial players in inflammatory disease and allograft rejection (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%